Signatures within esophageal microbiota with progression of esophageal squamous cell carcinoma - Li, Minjuan (Chin J Cancer Res, 2020)
OBJECTIVE: Esophageal squamous cell carcinoma (ESCC) is one of the dominant malignances worldwide, but currently there is less focus on the microbiota with ESCC and its precancerous lesions. METHODS: Paired esophageal biopsy and swab specimens were obtained from 236 participants in Linzhou, China. Data from 16S ribosomal RNA gene sequencing were processed using quantitative insights into microbial ecology (QIIME2) and R Studio to evaluate differences. The Wilcoxon rank sum test and Kruskal-Wallis rank sum test were used to compare diversity and characteristic genera by specimens and participant groups. Ordinal logistic regression model was used to build microbiol prediction model. RESULTS: Microbial diversity was similar between biopsy and swab specimens, including operational taxonomic unit (OTU) numbers and Shannon index. There were variations and similarities of esophageal microbiota among different pathological characteristics of ESCC. Top 10 relative abundance genera in all groups include Streptococcus, Prevotella, Veillonella, Actinobacillus, Haemophilus, Neisseria, Alloprevotella, Rothia, Gemella and Porphyromonas. Genus Streptococcus, Haemophilus, Neisseria and Porphyromonas showed significantly difference in disease groups when compared to normal control, whereas Streptococcus showed an increasing tendency with the progression of ESCC and others showed a decreasing tendency. About models based on all combinations of characteristic genera, only taken Streptococcus and Neisseria into model, the prediction performance was the ideal one, of which the area under the curve (AUC) was 0.738. CONCLUSIONS: Esophageal biopsy and swab specimens could yield similar microbial characterization. The combination of Streptococcus and Neisseria has the potential to predict the progression of ESCC, which is needed to confirm by large-scale, prospective cohort studies.